1H‐MRS in glutaric aciduria type 1: impact of biochemical phenotype and age on the cerebral accumulation of neurotoxic metabolites. Issue 5 (10th April 2015) - Harting, Inga; Boy, Nikolas; Heringer, Jana; Seitz, Angelika; Bendszus, Martin; Pouwels, Petra J.W.; Kölker, Stefan
Abstract: Background: In glutaric aciduria type 1 (GA1) the neurotoxic metabolites glutaric acid (GA) and 3‐hydroxyglutaric acid (3‐OH‐GA) accumulate within the brain. Due to limited efflux across the blood–brain‐barrier biochemical monitoring of intracerebrally accumulating toxic metabolites is as yet not possible. Aims: To investigate brain metabolic patterns in glutaric aciduria type 1 using 1 H magnetic resonance spectroscopy ( 1 H‐MRS) with focus on detecting the disease‐related neurotoxic metabolites GA and 3‐OH‐GA. Patients and methods: Short echo time 1 H‐MRS was performed in 13 treated metabolically stable patients. Twenty‐one white matter and 16 basal ganglia spectra from 12 patients (age range 7 months – 22 years) were included. Subgroups based on age, biochemical phenotype and/or associated MRI changes were compared with control spectra. Results: GA was elevated in white matter of patients. 3‐OH‐GA was elevated in white matter of older patients with associated signal changes on MRI, which was structurally characterized by decreased creatine and phosphocreatine (tCr) and elevated choline (Cho). Metabolite changes differed with biochemical phenotype and disease duration: Low excretors with up to 30 % residual enzyme activity had only mildly, non‐significantly elevated GA and mildly subnormal N‐acetylaspartate (tNAA). High excretors with complete lack of enzyme activity had significantly increased GA, tNAA was mildly subnormal in younger and decreased in older high excretors. Conclusions: GA and 3‐OH‐GA are detectable by in vivo 1 H‐MRS, which might finally allow biochemical follow‐up monitoring of intracerebrally accumulating neurotoxic metabolites in GA1. A high excreting phenotype appears to be a risk factor for cerebral GA accumulation and progressive neuroaxonal compromise despite a similar clinical course in younger high and low excreting patients. This might have consequences for long‐term outcome.